Financial intermediation costs in a dual banking system: the role of Islamic banking - Ibrahim, Mansor H.; Law, Siong Hook (Bank Indonesia, 2020)
This paper empirically analyses the role of Islamic banking in financial intermediation costs as measured by net interest margins for a leading dual banking country, Malaysia. Controlling for theoretically motivated determinants of the margins, the paper compares the interest/financing margins of conventional and Islamic banks and examines the impacts of Islamic banking presence on bank margins. The analysis provides evidence of the higher margins of Islamic banks compared to those of conventional banks. Further, the difference in bank margins between the two types of banks can be attributed to differences in market power, operating costs, and diversification. Finally, Islamic banking presence or penetration, as represented by the ratio of Islamic financing to aggregate bank credit/financing and, alternatively, the share of Islamic banking assets, is robustly associated with lower bank margins, on average. These results bear important implications for the development of the Islamic banking industry and in fostering the efficient allocation of financial resources by the banking system.